The Velocity Impact Response Of Filled And Unfilled Polypropylene Honeycomb Core Sandwich Structure - Ahmad, Mohamad Ibrahim (2016)
In this study, the performance of polypropylene honeycomb structure with different thickness, filled and unfilled was investigated. The density of the specimen was measured and subjected to flexural test, indentation test, compression and the low velocity impact test. After each test, the specimen was scanned under ultrasonic C-scan to investigate the effect of energy on the honeycomb panel structure. Introducing reinforced material into honeycomb cell increases the density of the panel structure up to 30 - 34% of initial density. Based on the flexural study, the percentage of energy increment for structure to collapse is around 15 to 38 percent for 30 mm core thickness and 6 to 17 percent for 40 mm core thickness. In indentation test, the n value is between 1.52 to 1.87 for 30 mm core thickness and 0.33 to 1.27 for core thickness 40 mm; 1.5 is the value for an acceptant for composite. The stiffness C was found to depend on the plastic collapse strength of the polyurethane foam and the properties of the skin. The value is between (0.90 to 1.56) x106 N/mn. In compression test, reinforced Polypropylene honeycomb filled sandwich structure has better energy absorption characteristic rather than Polypropylene honeycomb unfilled sandwich structure. In low velocity impact test, the reinforced effect increased the energy absorbtion efficienty about 10 to 30 percentage for both 30 mm and 40 mm core thickness. The damage area for all specimens for the Polypropylene honeycomb unfilled sandwich structure much higher compared to reinforce structure. The reinforced material acted to reduce the stress on the facing skin of the honeycomb structure.